The Descent of Mind / Psychological Perspectives on Hominid Evolution - Corballis Michael C; Lea Stephen E.G (Oxford University Press, 2004)
A thorough overview of what is known of the non-primate mind and its evolution. Are Humans Special? A History of Psychological Perspectives, The Background to Hi Mind Intelligence, Phylogeny from Apes to Humans, Human Cognitive Evolution, Predicting Hominid Intelligence from Brain Size, Perception of Personality Traits and Semantic Learning in Evolving Hominids, Preconditions for the Evolution of Protolanguages, The Role of Gesture and Mimetic Representation in Making Language the Province of Speech, The Evolution of Deep Social Mind in Humans, The Rise of the Meta Mind, The Evolution of a Theory of Mind, The Evolution of Certain Novel Human Capacities, Social Influences on Human Assortative Mating, Index.